1992
DOI: 10.1016/0741-5214(92)90226-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of pulmonary embolism in ambulant patients with pelvic vein thrombosis: A prospective study

Abstract: One hundred thirty-nine consecutive patients (average age 70.1 years) who were able to walk with a swollen leg were seen at the clinic where diagnosis of acute deep vein thrombosis (DVT) extending to the pelvis was confirmed by injecting microspheres labeled with technetium 99m into the dorsal foot vein (radionuclide venography). Thirty-nine (28%) of these patients had malignant disease. Perfusion lung scans performed immediately after radionuclide venography were supplemented by inhalation scans (99mTc-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
3
21
2
14
Order By: Relevance
“…Others studies using the criteria of Biello et al 13 or PIOPED 12 for ventilation perfusion scan analysis have reported similar results, 2-7 but they differed from our study by the type of DVT, location of the thrombosis, and methods used for diagnosing DVT. [2][3][4][5][6][7] In addition, our study underlines that, among patients who have abnormal scans, the proportion of high-probability scans is higher in patients younger than 30 years. Evaluating various methods of scan analysis, our study also indicates that the frequencies of high-probability patients in this population are similar when the perfusion scans are compared with chest radiographs or with ventilation scans.…”
Section: Commentmentioning
confidence: 82%
“…Others studies using the criteria of Biello et al 13 or PIOPED 12 for ventilation perfusion scan analysis have reported similar results, 2-7 but they differed from our study by the type of DVT, location of the thrombosis, and methods used for diagnosing DVT. [2][3][4][5][6][7] In addition, our study underlines that, among patients who have abnormal scans, the proportion of high-probability scans is higher in patients younger than 30 years. Evaluating various methods of scan analysis, our study also indicates that the frequencies of high-probability patients in this population are similar when the perfusion scans are compared with chest radiographs or with ventilation scans.…”
Section: Commentmentioning
confidence: 82%
“…[12][13][14][15][16][17][18][19] Patients with DVT subjected to CDT are generally young and otherwise healthy and presumably have a large cardiopulmonary reserve. Therefore, PE in this patient group is probably more likely to occur silently, both in general and during endovascular interventions in the inferior vena cava.…”
Section: Discussionmentioning
confidence: 99%
“…About half of patients with symptomatic proximal DVT have clinically silent PE at the time of diagnosis, 6 and 10% have symptomatic PE 7 , 8 . The prevalence of PE increases with age, particularly above 70 years 7 , 8 …”
Section: Natural Historymentioning
confidence: 99%